Statistical independence of escalatory ecological trends in Phanerozoic marine invertebrates - Kießling, Wolfgang; et al. (Science, 2006)
Ecological interactions, such as predation and bioturbation, are thought to be fundamental determinants of macroevolutionary trends. A data set containing global occurrences of Phanerozoic fossils of benthic marine invertebrates shows escalatory trends in the relative frequency of ecological groups, such as carnivores and noncarnivorous infaunal or mobile organisms. Associations between these trends are either statistically insignificant or interpretable as preservational effects. Thus, there is no evidence that escalation drives macroecological trends at global and million-year time scales. We also find that taxonomic richness and occurrence data are cross-correlated, which justifies the traditional use of one as a proxy of the other.
UnivIS-Import:2015-04-14:Pub.2006.nat.dgeo.IGM.LP.statis